(untitled) (Research, Society and Development, 2022)
Objective: To investigate the forms of treatment of migraine symptoms. Methods: This is a qualitative bibliographic review, which used the keywords "migraine" and "treatment" in Portuguese and English. It obtained articles from the Up to Date, Pubmed, Scielo and Medline databases between 2010 and 2020. Results: Migraine is characterized by the presence or absence of aura in addition to the appearance of throbbing pain of unilateral location in most cases with presence of nausea, photophobia and phonophobia. It, popularly known as migraine, is present in 15 to 25% of the population, being the second most common form of headache, behind only tension headache. There are many risk factors and mechanisms for the development of migraine. As well as, its possible classifications that are based on clinical diagnosis, based on them, the specific therapeutic approach is based on lifestyle changes, complementary therapies and pharmacotherapy. Conclusion: The treatment of migraine if applied at the right time prevents disease progression and ensures a better quality of life for patients.